Issues in International Exchange and Payments Systems - Quirk, Peter (World Economic and Financial Surveys; World Economic and Financial Surveys, 1995)
The global trend toward lilberalization in countries international payments and transfer systems has been widespread in both industrial and developing countries and most dramatic in Central and Eastern Europe. Countries in general have brought their exchange systems more in line with market principles and moved toward more flexible exchange rate arrangements. This study updates previous studies published under the title Developments in International Exchange and Payments Systems.